2018
DOI: 10.1371/journal.pone.0193368
|View full text |Cite
|
Sign up to set email alerts
|

Joint association between body fat and its distribution with all-cause mortality: A data linkage cohort study based on NHANES (1988-2011)

Abstract: ObjectiveAlthough obesity is recognized as an important risk of mortality, how the amount and distribution of body fat affect mortality risk is unclear. Furthermore, whether fat distribution confers any additional risk of mortality in addition to fat amount is not understood.MethodsThis data linkage cohort study included 16415 participants (8554 females) aged 18 to 89 years from National Health and Nutrition Examination Survey III (1988–1994) and its linked mortality data (31 December 2011). Cox proportional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…In contrast to the general population, patients with CHD demonstrate an inverse relationship between BMI and mortality, termed the obesity paradox [32]. However, it is now apparent that this paradox is related to the preservation of lean muscle mass as there is no paradox in the general population [33] or patients with CHD [27] when measuring body fat percentage instead of BMI. This point helps to understand how MetS parameters were improved in our HIIT patients, even in the absence of BMI changes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the general population, patients with CHD demonstrate an inverse relationship between BMI and mortality, termed the obesity paradox [32]. However, it is now apparent that this paradox is related to the preservation of lean muscle mass as there is no paradox in the general population [33] or patients with CHD [27] when measuring body fat percentage instead of BMI. This point helps to understand how MetS parameters were improved in our HIIT patients, even in the absence of BMI changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, researchers highlighted the link between high body fat content and mortality. Reducing body fat instead of total weight seems to benefit the cardiovascular system more than a decrease in body mass index [29]. The results of these studies indicated the health impact of physical activity on the health of amateurs.…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, using computed tomography (CT)-measured body fat, including both visceral and subcutaneous fat area, Lee et al [ 23 ] showed that only the visceral-to-subcutaneous fat area ratio (VSR) was independently associated with overall mortality in the fully adjusted model with age, sex, comorbidities and total fat mass. In another study using data from NHANES, Dong et al [ 24 ] demonstrated that both amount of body fat and body fat distribution (measured via WHR) were independently associated with overall mortality and the effect was sex-dependent.…”
Section: Discussionmentioning
confidence: 99%